Discovering the information professional: organisational culture in a digital world - Preston, H.; Allmand, M. (Emerald Publishing Limited, 2001)
This paper looks at issues regarding the place of the information professional in organisations where change processes are technologically driven or aided by technology. The case study examines the changing use of information sources by managers within the International Service for National Agricultural Research (ISNAR) in The Hague, The Netherlands. The emphasis was on technologically driven change, principally digitisation and access to external electronic resources. The findings highlight the vulnerability of ISNAR in the environment of organisational change, but also the success of the library in being an acknowledged source of quality information rather than simply a repository for any information which is available. The results of the survey showed that the library recognises that users who are familiar with electronic access to external sources will very often expect similar access to internal sources. A participative action research methodology was used.